THE EXPANSIVE CHALLENGES OF NGOs IN DEVELOPING COUNTRIES:CASE STUDY FROM NIGERIA - ONYELIKE CHUKWUNYERE DANIEL (Graduate School of International Studies Ajou University, 2019)
ABSTRACT` In the present compounding economy, an ever-increasing number of individuals wind up looking for assistance through the administrations of NGOs. Families are in declining circumstances and the requirement for viable and productive philanthropic human administrations is becoming quicker as more individuals are put out of work. Unmistakably the NGOs in developing countries must figure out how to hold effectively prepared workers to fight off the expense of finding and preparing substitutions. It is anything but difficult to think that NGO employees would remain if just their pay rates were to increment, be that as it may, the literature review and the research found that isn't the situation. While more cash would be invited, most NGO representatives did not get into the field to end up affluent, rather they joined the charitable association as a result of the mission and the longing to help individuals. Additionally, employee retention is likewise an indispensable test to all association in this day and age. there are quantities of elements which elevate the employees to remain or leave the organization. this study's objective is to establish employee retention strategies to be used by NGOs in developing countries funding and poor maintenance of workers have been a noteworthy test of Africare Nigeria. The study likewise demonstrates how Africare hotspot for reserve, its relationship with other organization, system towards accomplishing its targets. The study additionally prescribes that association should utilize systems to the hotspot for assets and hold its manager. For without this factor been tended to, the mission and targets of Africare Nigeria will be undermined.
학위논문(석사)--Graduate school of International Studies Ajou University :NGO학과,2019. 8